The choice of corporate social responsibility strategies under rivalry: Whether to increase socially responsible product characteristics or enhance relationship with buyers - Xiaoyang Zhao (PLoS ONE, 2026)
Corporate social responsibility (CSR) theory emphasizes both CSR characteristics in products and CSR activities to enhance relationships with buyers. However, there are theoretical gaps regarding the factors that influence firms’ CSR strategy choices in a competitive setting. This study develops a biform game model to study the trade-off between product-oriented strategies and relationship-oriented CSR strategies. The model demonstrates that factors such as information asymmetry, product value, market segment size, transaction costs, bargaining power, and other market conditions significantly influence firms’ CSR strategies. It identifies conditions under which strategic heterogeneity, strategic homogeneity, and a parameter space with multiple strategic heterogeneity equilibria can exist. When the value derived from product- and relationship-oriented strategies is significantly high, firms tend to adopt these respective strategies. In a low information asymmetry context, firms with lower bargaining power are more likely to choose a relationship-oriented strategy, whereas in a high information asymmetry context, these firms are inclined to adopt a product-oriented strategy. Regardless of the level of information asymmetry, firms with larger market scales tend to favor a product-oriented strategy. Additionally, the model integrates the synergy between business strategy and CSR strategy, which further shapes the trade-offs firms encounter in their CSR strategy choices. This study offers new insights into CSR strategy choices and the resulting market outcomes in competitive environments.